Three‐dimensional analysis of craniofacial morphology in patients with pycnodysostosis. (28th February 2021) - Ferlias, Nikolaos; Gjørup, Hans; Aagaard Doherty, Mia; Haagerup, Annette; Klit Pedersen, Thomas
Abstract: Objective: To perform a 3D cephalometric analysis of the craniofacial characteristics of patients with pycnodysostosis and compare this with a matched control group. Setting and Sample population: This cross‐sectional descriptive study assessed eight CBCTs obtained in patients with pycnodysostosis (4 males, 4 females, mean age: 31.8 years). Materials and methods: Eight Danish patients with pycnodysostosis were seen at the University's Orthodontic Clinic. All CBCTs were analysed using the Mimics 21.0 software (Materialise®, Belgium) and compared with a control group (6 males, 8 females, mean age: 33.6 years). Results: Interclass correlation coefficient showed excellent intra‐rater reliability (> 0.93). All measurements in the 3D cephalometric analysis revealed statistical significance ( P < .05) when compared with controls. Patients with pycnodysostosis generally had significantly smaller maxilla in the transverse ( P < .001), sagittal ( P < .002) and vertical ( P < .001) dimensions. Their mandibles were also smaller vertically ( P < .001) and in length ( P < .001). Gonial angle was significantly larger than controls ( P < .001), while mandibular volumes were considerably smaller ( P < .001). Conclusion: Patients with pycnodysostosis have significantly smaller jaws in the vertical, sagittal and transverse dimensions compared with controls. Furthermore, the gonial angle was significantly larger, while the volume of the mandible was significantly smaller.